El paseo de Rosita - Hutchins, Pat, 1942-2017. (New York : Scholastic, 1995)
The story of Rosie the hen, who is unaware that the fox is following her.
Keywords: Animals -- Fiction; Chickens -- Fiction; Spanish language materials; Animaux -- Romans, nouvelles, etc; Animals; Chickens; Fiction